Roles of the Brassica napus DELLA Protein BnaA6.RGA, in Modulating Drought Tolerance by Interacting With the ABA Signaling Component BnaA10.ABF2 - Wu, Jiajing; Yan, Guanbo; Duan, Zhiqiang; Wang, Zhijuan; Kang, Chunying; Guo, Liang; Liu, Kede; Tu, Jinxing; Shen, Jinxiong; Yi, Bin; Fu, Tingdong; Li, Xia; et al. (Frontiers in Plant Science, 2020)
Drought is a major threat to plant growth and crop productivity. Reduced level of the gibberellin would result in increased drought tolerance, but the underlying mechanism is still unclear. In Brassica napus, there are four BnaRGA genes that code for DELLA proteins, negative regulators of GA signaling. Among them, expression of BnaA6.RGA was greatly induced by drought and abscisic acid (ABA). Previously, we created the gain-of-function mutant of BnaA6.RGA, bnaa6.rga-D, and the loss-of-function quadruple mutant, bnarga by CRISPR/Cas9, respectively. Here we show that bnaa6.rga-D displayed enhanced drought tolerance, and its stomatal closure was hypersensitive to ABA treatment. By contrast, bnarga displayed reduced drought tolerance and was less sensitive to ABA treatment, but there is no difference in drought tolerance between single BnaRGA mutant and WT, suggesting a functional redundancy between the BnaRGA genes in this process. Furthermore, we found that BnaRGAs were able to interact physically with BnaA10.ABF2, an essential transcription factor in ABA signaling. The BnaA10.ABF2-BnaA6.RGA protein complex greatly increased the expression level of the drought responsive gene BnaC9.RAB18. Taken together, this work highlighted the fundamental roles of DELLA proteins in drought tolerance in B. napus, and provide desirable germplasm for further breeding of drought tolerance in rapeseed.